Cloning and Expression of Randomly Mutated Bacillus subtilisα-Amylase Genes in HB101. (24th July 2011) - Rabbani, Mohammed; MirMohammad Sadeghi, Hamid; Moazen, Fatemeh; Rahimi, Mehran; Salehi, Golnaz
Abstract : The aim of this study was to isolate and express the randomly mutated α - amylase gene from B. subtilis strain 168. BS168F: 5′-gtgtcaagaatgtttgc-3′ and BS168R: 3′-gttttgttaaaagatga-5′ primers were used to amplify the amylase gene using the following cycle in error-prone PCR method: 94°C for 30 s, 40°C for 2 min, and 72°C for 2 min in 30 cycles that were followed with 72°C for 2 min as a post cycle. E. coli XL1 blue was used as host for plasmid construction. Amylase enzyme activity assay was performed using continuous spectrophotometric procedures. Results of sequencing showed that sequence was cloned from the first ATG and with the correct open reading frame. Having confirmed the integrity of the insert, the gene was ligated into expression vector pET-15b and then further confirmed using digestion analysis. Amylase activity showed 3 clones with higher enzymatic activity compared with the wild type. Error-prone PCR method produced a mutated gene that provides amylase activity much higher than that of wild type. Sequencing the mutated genes should shed light on the important region of the genes that could be manipulated in future studies.